Nursing diagnoses of impaired memory and chronic confusion for older adults: diagnostic content validation - Priscilla Alfradique de Souza; Kay Coalson Avant; Andrea E. Berndt (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To validate the defining characteristics of the nursing diagnoses, impaired memory and chronic confusion for older adults, by testing diagnostic concept definitions among expert nurses. Methods: We used a Diagnostic content validation using an online survey of expert clinical nurses. Results: 195 expert nurses performed the diagnostic validations. Findings provided validity of impaired memory with 11 major defining characteristics and chronic confusion, with 11 major and one minor defining characteristics. In both diagnoses, content validity index was 0.85. Factor analysis provided four and five supported factors for impaired memory and chronic confusion, respectively. Conclusion: The study provided evidence of validity of the two diagnoses and made them clearer. Using these updated nursing diagnoses, nurses have the potential to improve accuracy and quality of care for elderly patients, contributing to more accurate nursing gerontological care.